(untitled) (Damascus University Journal of agriculture sciences, 2021)
44 Bemisia tabaci populations were collected from various hosts at Syrian coast to detected genetic diversity and indicators using ISSR and ten primers. Six out of them was successes and gave 105 amplification fragments with 75.24% polymorphic percentage. Polymorphism percentage was ranged between 50% (ISSR-1) and 100% (ISSR-10). The rate of polymorphic loci (PPB) for all studied populations was 53%, the number of alleles per locus (N0) was 1.89, the effective number of alleles (NE) was 1.41, and the genetic diversity (HE) was 0.18. The genetic similarity ranged between 97.2% (SyBt23 & SyBt21) and 57% (SyBt43 & SyBt6). Shannon’s index (I) of populations was 0.129 (SyBt30) and 0.272 (SyBt39). The phylogenetic tree was divided into four main groups, and it turns out that the heights of sea level were affected on the distribution of populations.